POLA PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN RAWAT INAP RSUD ANUTAPURA PALU - Budiawan, Erick; Gloria, Yovanka Lista; Wulandari, Ayu (Universitas Imelda Medan, 2023)
This study aims to determine the pattern of antidiabetic treatment and the accuracy of the use of antidiabetic drugs based on indications, drugs, patients, and doses of use at Anutapura Hospital Palu. This study is a descriptive research method using a cross-sectional method with retrospective data collection based on medical record data for type 2 Diabetes mellitus patients in 2021. Sampling was carried out using a minimized sampling technique with medical record data of 30 patients based on inclusion criteria. The results of this study are patients with Type 2 Diabetes Mellitus, which are female, as many as 16 patients (54%), in the age range of 48-60 years as many as 14 patients (46%), the most widely used oral antidiabetic drug group is Biguanid group (Metformin) as many as 18 patients (70%), the type of insulin drug that was most widely used was Novorapid as many as 13 patients (61.91%), and adjunctive drugs with the highest use of therapy, namely Amlodipine as many as 14 patients with a percentage (7, 4%). Antidiabetic treatment is based on the right indication (100%), right drug (50%), right patient (93%) and right dose (100%).